Dampak Pemahaman Konsep Perkalian Bilangan Bulat pada Peserta Didik - Ikbal, Mohamad; Nursupiamin, Nursupiamin; Yulia, Yulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to describe the level of conceptual understanding of integer multiplication among students at MTs Nida’ul Khairaat Pombewe and to analyze its impact on their ability to solve mathematical problems. The research employed a descriptive qualitative approach using diagnostic tests, semi-structured interviews, observations, and documentation as data collection techniques. A total of 31 students participated in a test measuring four indicators of conceptual understanding: classification, concept connection, algorithm, and representation. The results showed that 80% of students were in the low understanding category, 15% in the moderate category, and only 5% in the high category. In-depth analysis of three representative subjects revealed that students in the high category demonstrated strong relational understanding, those in the moderate category showed partial understanding, while students in the low category experienced fundamental misconceptions, particularly regarding sign rules and mathematical representations. The findings also indicated that representation—especially visual and contextual—was the weakest aspect for most students. Interviews confirmed that the teacher’s teaching methods, particularly the pace of explanation and lack of repetition, significantly influenced conceptual understanding. This study concludes that strengthening conceptual understanding should be carried out through more concrete, gradual, and representation-based learning to prevent misconceptions and improve students’ ability to solve integer multiplication problems. Keywords: Conceptual Understanding; Integers; Multiplication; Misconception; Mathematical Representation; Mathematics Learning